Antinociceptive and anti-inflammatory activities of the aqueous leaf extract of Erlangea tomentosa (Asteraceae) in rats and mice - Muhwana, Isaac; Obakiro, Samuel Baker; Ibanda, Ivan; Crucifix, Pender Gift; Moyosore Afodun, Adam; Odoma, Saidi (Journal of Pharmacy & Bioresources, 2020)
Erlangea tomentosa (Asteraceae) is used traditionally in the preparation of herbal remedies for management of several diseases including pain and inflammation. However, its efficacy and safety have not been scientifically validated. The aim of this study was to investigate the antinociceptive and anti-inflammatory activities of the aqueous leaf extract of this plant and its acute toxicity profile in animal models. Antinociceptive activity and anti-inflammatory activity were determined using the acetic acid-induced writhing model in mice and carrageenan induced inflammation model in rats respectively. The oral median lethal dose (LD50) was determined using the Lorke’s Method. The extract inhibited pain due to acetic acid significantly (p<0.05) at doses of 250 mg/kg and 500 mg/kg. The inflammation due to carrageenan was also significantly (p<0.05) reduced at dose of 500 mg/kg body weight but not 250 mg/Kg. The LD50 value of the extract was greater than 5,000 mg/kg implying that the extract was safe in 24 hours when administered in a single high oral dose. Preliminary phytochemical screening revealed the presence of alkaloids, anthraquinones, coumarins, saponins, tannins and resins. The present study has demonstrated the antinociceptive and anti-inflammatory potential of aqueous leaf extract of Erlangea tomentosa in rats and mice; thus validates the folkloric use of the plant.
Keywords: Erlangea tomentosa; Antinociception; Anti-inflammation; Acetic acid; Carrageenan